Establishment and Characterization of an Irinotecan-Resistant Human Colon Cancer Cell Line - Wu, Zhuo-Xun; Yang, Yuqi; Zeng, Leli; Patel, Harsh; Bo, Letao; Lin, Lusheng; Chen, Zhe-Sheng (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is a leading cause of cancer-related deaths worldwide. Irinotecan is widely used as a chemotherapeutic drug to treat CRC. However, the mechanisms of acquired resistance to irinotecan in CRC remain inconclusive. In the present study, we established a novel irinotecan-resistant human colon cell line to investigate the underlying mechanism (s) of irinotecan resistance, particularly the overexpression of ABC transporters. The irinotecan-resistant S1-IR20 cell line was established by exposing irinotecan to human S1 colon cancer cells. MTT cytotoxicity assay was carried out to determine the drug resistance profile of S1-IR20 cells. The drug-resistant cells showed about 47-fold resistance to irinotecan and cross-resistance to ABCG2 substrates in comparison with S1 cells. By Western blot analysis, S1-IR20 cells showed significant increase of ABCG2, but not ABCB1 or ABCC1 in protein expression level as compared to that of parental S1 cells. The immunofluorescence assay showed that the overexpressed ABCG2 transporter is localized on the cell membrane of S1-IR20 cells, suggesting an active efflux function of the ABCG2 transporter. This finding was further confirmed by reversal studies that inhibiting efflux function of ABCG2 was able to completely abolish drug resistance to irinotecan as well as other ABCG2 substrates in S1-IR20 cells. In conclusion, our work established an in vitro model of irinotecan resistance in CRC and suggested ABCG2 overexpression as one of the underlying mechanisms of acquired resistance to irinotecan. This novel resistant cell line may enable future studies to overcome drug resistance in vitro and improve CRC treatment in vivo.